Impact of Osteoarthritis on Difficulty Walking: A Population‐Based Study. Issue 1 (15th December 2017) - King, Lauren K.; Kendzerska, Tetyana; Waugh, Esther J.; Hawker, Gillian A.
Abstract : Objective: To assess the relationship of hip and knee osteoarthritis (OA) to walking difficulty. Methods: A population cohort ages ≤55 years recruited from 1996 to 1998 (n = 28, 451) completed a standardized questionnaire assessing demographics, health conditions, joint symptoms, and functional limitations, including difficulty walking in the past 3 months. Survey data were linked to health administrative databases; self‐report and administrative data were used to identify health conditions. Hip/knee OA was defined as self‐reported swelling, pain, or stiffness in a hip or knee lasting ≥6 weeks in the past 3 months without an inflammatory arthritis diagnosis. Using multivariable logistic regression, we examined the determinants of walking difficulty and constructed a clinical nomogram. Results: A total of 18, 490 cohort participants were eligible (mean age 68 years, 60% women), and 25% reported difficulty walking. Difficulty walking was significantly and independently associated with older age, female sex, body mass index, and several health conditions. Of the conditions examined, the likelihood of walking difficulty was greatest with hip and knee OA and increased with the number of hip/knee joints affected. The predicted probability of difficulty walking for a 60‐year‐old middle‐income, normal‐weight woman was 5–10% with no health conditions, 10–20% with diabetes mellitus and cardiovascular (CV) disease, 40% with OA in 2 hips/knees, 60–70% with diabetes mellitus, CV disease, and OA in 2 hips/knees, and 80% with diabetes mellitus, CV disease, and OA in all hips/knees. Conclusion: In a population cohort, symptomatic hip/knee OA was the strongest contributor to walking difficulty. Given the importance of walking to engagement in physical activity for chronic disease management, greater attention to OA is warranted.